ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2020
DOI: 10.1109/icassp40776.2020.9054717
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent Directional Feedback Delay Network

Abstract: A recent publication introduced the Directional Feedback Delay Network, a parametric artificial reverberation algorithm capable of producing direction-dependent energy decay. This method extends the capabilities of Feedback Delay Networks by using multichannel delay-line groups and a spatial transform to produce direction-dependent reverberation in the Ambisonics domain. In this paper, we present a modified formulation of the Directional Feedback Delay Network method that allows both frequency-and direction-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…The set of K directions should be carefully selected as more directions will increase the computational complexity of the system, while a lower K value will smooth out the directional features. In a previous study, a set of 12 directions equally distributed around the sphere has been shown to offer satisfactory results [23].…”
Section: Directional Late Reverberationmentioning
confidence: 95%
See 4 more Smart Citations
“…The set of K directions should be carefully selected as more directions will increase the computational complexity of the system, while a lower K value will smooth out the directional features. In a previous study, a set of 12 directions equally distributed around the sphere has been shown to offer satisfactory results [23].…”
Section: Directional Late Reverberationmentioning
confidence: 95%
“…A DFDN [22], [23] is a delay network reverberator which extends the design of an FDN [11] to produce multichannel reverberation with directional decay characteristics. In a DFDN, each delay path contains a group of K delay lines to carry a multichannel signal (Fig.…”
Section: B Directional Feedback Delay Networkmentioning
confidence: 99%
See 3 more Smart Citations